Association of Polymorphisms in C-Reactive Protein (CRP) Promoter -821 A>G, -390 C>A/T, and Plasma Interferon-α (IFN-α) with Plasma CRP Level in Javanese Systemic Lupus Erythematosus (SLE) Patients - Awalia Awalia; Harianto Notopuro; Joewono Soeroso (Acta Medica Indonesiana)
Background: As an acute-phase reactant, CRP is needed to clear apoptotic cells and immune complexes in SLE. This unresponsive CRP may be caused by genetic variation and abundant IFN-α that might inhibit CRP secretion. This study aims to analyze the association of single nucleotide polymorphisms (SNP) in CRP promoter and plasma IFN-α with CRP level in Javanese SLE patients. We also analyzed the association of these SNPs with SLE. Methods: Forty SLE and 40 spondyloarthritis (as control) patients were included. SLE subjects underwent routine laboratory test, CRP level, serum IFN-α, and DNA sequencing to detect SNPs in CRP promoter. The control group only underwent DNA sequencing. Results: The median age of SLE patients was 31.5 years. The median SLAM score was 8.5. The median age of the control group was 39 years. The average CRP was 5.19 SD 2.69 mg/L, median plasma IFN-α was 46.02 pg/ml. There was no significant difference of SNPs in CRP -821 (rs2794521) or -390 (rs3091244) between SLE and control. New SNP was found in CRP -456 A>G in 5 SLE patients, but none in controls. This SNP would increase SLE risk 2.143 times. There was a moderate negative correlation between IFN-α level and plasma CRP. Linear regression only showed IFN-α level (not either SNP) correlated with serum CRP. Conclusion: Plasma IFN-α correlated with CRP level. There was no association of SNPs in CRP -821, -390, and -456 with CRP level. SNP CRP -456 A>G would increase the risk of SLE with an odds ratio of 2.143.